THE EFFECT OF PHOTOPERIODISM WITH LED LIGHT ON PRODUCTIVITY OF FEMALE FLOWER IN CUCUMBER (CUCUMIS SATIVUS L.) - Ikram, Muhammad Maulana; Esyanti, Rizkita Rachmi; Faizal, Ahmad (MATTER: International Journal of Science and Technology, 2015)
Cucumber productivity can be optimize by regulating their photoperiod. Photoperiod will affect the production of female flower, the basis for the production of cucumber fruit. In this research, two cucumber lines (Mercy and KE 27187) was treated with 8, 12, and 16 hours of light by using red light (λred = 630 nm), blue light (λblue = 460 nm), and yellow light (λyellow = 510 nm) LEDs. Treatment from 12 h of light increased sugar accumulation (7482, 69 ppm) but not too different compared to 8 hours and 16 hours treatment. It also produced ethylene 27, 69% (v/v). Meanwhile, 16 hours treatment in KE 27187 line produced highest sugar accumulation (9178, 59 ppm) and ethylene production (21,92% (v/v)). High sugar accumulation and ethylene production could increase the production of female flower. In addition, 16 hours treatment resulted in the highest growth rate (2-4 times higher) and biomass dry weight (2-6 times higher) than other treatments. These results valid for both lines, Mercy and KE 27187. Using this LED Technology, we predicted that Mercy is a short-day plant and KE 27187 is a long-day plant.